1993
DOI: 10.2134/agronj1993.00021962008500010001x
|View full text |Cite
|
Sign up to set email alerts
|

Core Cultivation of a Putting Green with Hollow and Solid Tines

Abstract: Most turfgrass soil cultivation research has emphasized water in· filtration and thatch responses, but has provided limited information regarding detailed soil and rooting responses to different cultivation methods. This study evaluated cultivation effects on soil physical properties and turf growth of a 'Penneagle' creeping bentgrass (Agrostis palustris Hods.) putting green. Cultivation, utilizing vertically operating hollow (HTC) or solid (STC) tines, was applied over a 3-yr period on a loamy sand soil (modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
104
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(113 citation statements)
references
References 13 publications
(20 reference statements)
4
104
5
Order By: Relevance
“…Spring-plus-summer coring resulted in increased chlorophyll levels as well as improved turf color and quality in late summer. Eggens, 1980;White and Dickens, 1984;Murphy et al, 1993;McCarty et al, 2005McCarty et al, , 2007. Murray and Juska (1977) observed that coring reduced total organic matter in the thatch of Kentucky bluegrass (Poa pratensis L.), but the eff ect was short-lived.…”
Section: Introductionmentioning
confidence: 99%
“…Spring-plus-summer coring resulted in increased chlorophyll levels as well as improved turf color and quality in late summer. Eggens, 1980;White and Dickens, 1984;Murphy et al, 1993;McCarty et al, 2005McCarty et al, , 2007. Murray and Juska (1977) observed that coring reduced total organic matter in the thatch of Kentucky bluegrass (Poa pratensis L.), but the eff ect was short-lived.…”
Section: Introductionmentioning
confidence: 99%
“…We speculate the greatest difference in soil physical properties was most prominent shortly after hollow tine or solid tine core cultivation; which diminished as roots grew, compaction dissipated, and core channels were covered or filled. Other researchers have reported greater air porosity and saturated water conductivity in turf managed with hollow tines compared to solid tines, and enhanced water infiltration in turf managed with hollow tine core cultivation compare to untreated turf (Murphy et al, 1992;Baldwin et al, 2006;McCarty et al, 2007).…”
Section: Turf: Golf Course Fairwaymentioning
confidence: 96%
“…Hydrographs revealed reduce runoff volumes associated with hollow tine core cultivation in 81% (63 d) and 87% (2 d) of the samples ( Figure 3B). Solid tine core cultivation has been shown to result in localized compaction with the most sever compaction at the base of the zone of cultivation (Murphy et al, 1992). Hollow tine core cultivation has also been shown to result in compaction along the sidewalls and base of the coring; however, sidewall compaction dissipated while bottom compaction remained after 95 d (Petrovic, 1979).…”
Section: Turf: Golf Course Fairwaymentioning
confidence: 99%
See 2 more Smart Citations